Evaluation of the Mrp2-mediated flavonoid-drug interaction potential of quercetin in rats and in vitro models - Ju-Hee Oh; Joo Hyun Lee; Young-Joo Lee (Elsevier, 2019)
Quercetin is a biologically active flavonoid that has been used as a popular health supplement. It is reported that quercetin may cause flavonoid-drug interaction mediated by P-glycoprotein, the most predominant efflux transporter. In this study, we comprehensively evaluated the potential of the pharmacokinetic interaction of quercetin mediated by multidrug resistance-associated protein 2 (MRP2), another major efflux transporter. MRP2-transfected MDCKII cells and LS174T cells were used to evaluate the potential inhibition and induction of MRP2 by quercetin in vitro. To evaluate the induction effect of quercetin on Mrp2 in vivo, Mrp2 mRNA expression in rat liver, kidney, and small intestinal tissues was determined after the oral administration of quercetin (50, 100, or 250 mg/kg) for seven days. Mrp2-mediated interaction potential was also evaluated by the pharmacokinetic study of phenolsulfonphthalein in rats after single or multiple doses of quercetin. Additionally, the effect of quercetin on absorption of docetaxel, a P-glycoprotein and CYP3A4 substrate, was also evaluated. Quercetin inhibited the function of MRP2 at 10 µM and induced the mRNA expression of MRP2 at 50 µM in vitro. Additionally, at 100 mg/kg, quercetin markedly increased Mrp2 expression in the small intestine of rats. However, there was no significant change in phenolsulfonphthalein pharmacokinetics due to single- (50, 100, or 250 mg/kg) or multiple-dose (50, 100, or 250 mg/kg for seven days) quercetin co-administration. By contrast, a significant interaction caused by quercetin (100 mg/kg) was observed in the absorption of docetaxel. The results suggested that although quercetin modulates the function and expression of MRP2 in vitro, it may have a low potential of Mrp2-mediated interaction and present negligible safety concerns related to the interaction. Keywords: Quercetin, P-glycoprotein, Multidrug resistance-associated protein 2, Pharmacokinetics, Flavonoid-drug interaction